Distribution and conservation status of Speleonycta ozarkensis (Insecta, Zygentoma, Nicoletiidae) from caves of the Ozark Highlands of Arkansas and Oklahoma, USA - Luis Espinasa; Monika Espinasa; Dante B. Fenolio; Michael E. Slay; Matthew Niemiller (Subterranean Biology, 2014)
The “thysanuran” (Zygentoma: Nicoletiidae) Speleonycta ozarkensis is the only troglobiotic nicoletiid from the Ozark Highlands. It was originally described with only four specimens from four different cave systems in Arkansas and Oklahoma. The scarcity of available specimens has made it difficult to determine whether morphological variation among populations represents intraspecific or interspecific variation. We examined molecular (16S rRNA) variation among populations and found no evidence that they represent a species complex. Because of its limited distribution and lack of ecological and life history data, S. ozarkensis may be a species of conservation concern. We therefore conducted a conservation status assessment. We bioinventoried 44 caves in Arkansas and Oklahoma to determine the distribution of S. ozarkensis. A new locality in Adair Co., Oklahoma, was discovered and new specimens were collected to better assess morphological variation among populations. Data on ecology and life history was gathered. We determined the conservation status of the species and identified potential threats to existing populations. Despite being known from a few localities, S. ozarkensis has a broad distribution approaching 10,000 km2. Molecular data suggest S. ozarkensis is capable of considerable dispersal and is primarily an epikarstic species, perhaps explaining why it has been infrequently collected from caves. Conservation assessments revealed that S. ozarkensis is at a slight risk of extinction. We identified seven threats impacting populations that vary in scope and severity, but only recreational caving (three caves) and development associated with urbanization (one cave) have the greatest potential to immediately impact populations.